Magnesium, zinc, and copper status in women involved in different sports - Nuviala, R. J.; Lapieza, M. G.; Bernal, E. (International Journal of Sport Nutrition and Exercise Metabolism, 1999)
The dietary intake, serum levels, and urinary excretion of magnesium, zinc, and copper were studied in 78 women involved in different sports (karate, handball, basketball, and running) and in 65 sedentary women. Seven-day, weighed-food dietary reports revealed that no group of female athletes reached the minimal intake recommended for magnesium (280 mg/day) and zinc (12 mg/day), although their values were superior to those of the control group. The estimated safe and adequate minimal intake of copper (1.5 mg/day) was amply surpassed by the basketball players and runners but was not reached by the handball players. Serum levels and urinary excretion of magnesium, zinc and copper di not seem related either to their intake or to the type of physical activity performed. The influence of other factors such as nutritional status, bioavailability, intestinal absorption mechanisms, and muscle-level modifications might explain the differences between the different groups of female athletes.